2007
DOI: 10.1529/biophysj.106.099762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholesterol on the Biophysical and Physiological Properties of a Clinical Pulmonary Surfactant

Abstract: Pulmonary surfactant is a complex mixture of lipids and proteins that forms a surface-active film at the air-water interface of alveoli capable of reducing surface tension to near 0 mN/m. The role of cholesterol, the major neutral lipid component of pulmonary surfactant, remains uncertain. We studied the physiological effect of cholesterol by monitoring blood oxygenation levels of surfactant-deficient rats treated or not treated with bovine lipid extract surfactant (BLES) containing zero or physiological amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
90
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 50 publications
(60 reference statements)
9
90
1
2
Order By: Relevance
“…Reasonably, the addition of cholesterol to clinical formulations will have an impact on the treatments of LS deficiency-related syndromes (e.g., neonatal respiratory distress syndrome). Several studies have reported negative effects of cholesterol on the performance of LSE (14,58), even though cholesterol is naturally present in the in vivo LS system. The rationale behind the reported negative effects of cholesterol remains unclear and the discrepancy may be related to differences other than the cholesterol content between the extracts and the in vivo system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reasonably, the addition of cholesterol to clinical formulations will have an impact on the treatments of LS deficiency-related syndromes (e.g., neonatal respiratory distress syndrome). Several studies have reported negative effects of cholesterol on the performance of LSE (14,58), even though cholesterol is naturally present in the in vivo LS system. The rationale behind the reported negative effects of cholesterol remains unclear and the discrepancy may be related to differences other than the cholesterol content between the extracts and the in vivo system.…”
Section: Resultsmentioning
confidence: 99%
“…The multilayer structure has been proposed to have arrangements similar to the bulk phases formed in LS extracts (LSEs) (6,(12)(13)(14) and in clinical multivesicular dispersions (15,16). Two types of multilayer structures have been observed: lamellar bodies with spherically concentric bilayers and a tetragonal structure called tubular myelin (6,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These LS are also found to have reduced surface activity, although the cause for this is not clear 11 . An early study by Haas and Longmore showed that although the lung can produce cholesterol much larger in amount than its own requirement, the main mechanism used in the production of surfactant cholesterol is the use of lipoprotein cholesterol supplied form the blood, since about 2 wt of the cholesterol is from endogenous synthesis 12 .…”
mentioning
confidence: 96%
“…However previous studies also suggest that excess cholesterol also has deleterious effects, e.g., it retards the achievement of minimum surface tension to near zero value during complete film compression and decrease of post collapse re-spreading 11 .…”
mentioning
confidence: 98%